Community Empowerment Through Transparency and Accountability of Village Funds as an Effort to Increase Resource Potential and Independence in Pematang Johar Village - Linda Wahyu Marpaung; Jefri Jefri; Yannuke Patricia Siahaan; Muhammad Hafiz Abd.Rashid; Sipnarong Kanchawongpaisan; Pan Bao Giang; Thierry Charlson Lohart (Eastasouth Journal of Effective Community Services, 2025)
This community service activity aims to strengthen transparency and accountability in the management of Village Funds as an effort to increase the potential of resources and independence of Pematang Johar Village, Deli Serdang Regency. The program is implemented through observation, socialization, implementation, and evaluation stages, which are designed to identify village needs, increase the capacity of officials, and strengthen technology-based village governance. The results of the activities show that Pematang Johar Village has a strong commitment to realizing good governance through the use of the Siskeudes application, the implementation of digital village services, and the capacity building of village officials in administrative and financial management. In addition, the potential for rice field ecotourism that is developing in the village contributes greatly to strengthening the local economy and empowering the community. Through strengthening transparency, accountability, and community participation, this program contributes to promoting village independence and supporting sustainable development.